2019
DOI: 10.1113/jp277590
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of non‐perfused sublingual capillaries increases microcirculatory oxygen extraction capacity throughout ascent to 7126 m

Abstract: Key pointsr A physiological response to increase microcirculatory oxygen extraction capacity at high altitude is to recruit capillaries. r In the present study, we report that high altitude-induced sublingual capillary recruitment is an intrinsic mechanism of the sublingual microcirculation that is independent of changes in cardiac output, arterial blood pressure or systemic vascular hindrance.r Using a topical nitroglycerin challenge to the sublingual microcirculation, we show that high altitude-related capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 48 publications
(61 reference statements)
4
47
0
Order By: Relevance
“…HVM imaging directly visualizes hemoglobin that is contained in red blood cells, as opposed to anatomical structures of the tissue, thereby defining the functional component of the microcirculation in terms of oxygen carrying capacity. Thus, the boundaries of microvascular structures within an HVM image sequence are defined by the spatial arrangement and direction of movement of red blood cells, and structures not currently perfused by red blood cells may only be visualized using recruitment maneuvers as described elsewhere 22 . These structures, which may be further categorized into arterioles, capillaries, and venules in subsequent steps, are referred to as “vessels” in the current manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…HVM imaging directly visualizes hemoglobin that is contained in red blood cells, as opposed to anatomical structures of the tissue, thereby defining the functional component of the microcirculation in terms of oxygen carrying capacity. Thus, the boundaries of microvascular structures within an HVM image sequence are defined by the spatial arrangement and direction of movement of red blood cells, and structures not currently perfused by red blood cells may only be visualized using recruitment maneuvers as described elsewhere 22 . These structures, which may be further categorized into arterioles, capillaries, and venules in subsequent steps, are referred to as “vessels” in the current manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…Patients severely affected with COVID-19 develop fever and hypoxemia. Therefore, hypoxia-induced capillary recruitment could be an explanation for the increased vascular density observed [ 9 , 10 ]. Besides, high metabolic activity and tissue hypoxia are recognized stimuli for vascular growth [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies concerning the effects of hypoxia on the microcirculatory system are comparatively scarce. For example, previous studies reported an increase in sublingual microcirculatory blood flow and capillary density after ascent to high altitudes 19,20 , which suggests microvascular recruitment after exposure to hypobaric hypoxia 21 . However, recent studies also reported that the physiological adaptions to hypobaric hypoxia can differ substantially from those to normobaric hypoxia 22,23 , which is why the results of studies conducted in high altitude can not be fully applied to the normobaric environment.…”
Section: Llsmentioning
confidence: 96%